Arsitektur Inklusif Sebagai Tanggapan Bagi Jamaah Disabilitas Masjid Al Kamil Panenjoan Sumedang - Baiezt, Ivan Zubeil; Barliana, Mokhamad Syaom (Jurnal Talenta Sipil, 2024)
A mosque is a building where Muslims carry out mass/congregational or individual worship, as well as other activities related to Islamic culture. Mosques have an important role in accommodatang all the needs of their users without exception. Congregants who come are not only adults but children, men and women, people with disabilities with all their limitations. Several facilities for people with disabilities have been provided but need to be improved for comfort. and user safety. So, a real solution is needed to be able to solve this problem. In architecture, there is an approach known, namely inclusive architecture which highly upholds the equal rights of every individual in their activities and activities in the Al Kamil Panenjoan Sumedang Mosque. The lack of guiding blocks and signage will certainly make it difficult for pilgrims to come, especially for people with disabilities. By implementing inclusive architecture at the Al Kamil Panenjoan Sumedang Mosque, it is hoped that it can accommodate and facilitate accessibility to this area, especially for people with disabilities.